Use of CBL exon 8 and 9 mutations in diagnosis of myeloproliferative neoplasms and myelodysplastic/myeloproliferative disorders: an analysis of 636 cases - Schnittger, Susanne; Reiter, Andreas (Haematologica, the hematology journal, 2012)
We analyzed 636 patients with diverse myeloproliferative neoplasms or myelodysplastic/myeloproliferative neoplasms for mutations of the Casitas B-cell lymphoma gene (CBLmut) in exons 8 and 9 and performed correlations to other genetic alterations. CBLmut were detected in 63 of 636 (9.9%) of these selected patients. CBLmut were more frequent in myelodysplastic/myeloproliferative neoplasms than myeloproliferative neoplasms (51 of 328, 15.5% vs. 12 of 291, 4.1%; P<0.001). Frequency was 48 of 278 (17.3%) in chronic myelomonocytic leukemia and 3 of 33 (9.1%) in unclassifiable myelodysplastic/myeloproliferative neoplasms. CBLmut was not detected in polycythemia vera, primary myelofibrosis, essential thrombocythemia, or refractory anemia with ring sideroblasts and marked thrombocytosis. CBLmut were underrepresented in JAK2V617F mutated as compared to JAK2V617wt cases (P<0.001), and mutually exclusive of JAK2exon12mut and MPLW515mut. CBLmut were associated with monosomy 7 (P=0.008) and TET2mut (P=0.003). In chronic myelomonocytic leukemia, CBLmut had no significant impact on survival outcomes. Therefore, CBLmut are frequent in chronic myelomonocytic leukemia, absent in classical myeloproliferative neoplasms, and are only exceptionally found in coincidence with JAK-STAT pathway activating mutations.